Design Integration, Development and Functional Verification of Communication System Between DC Charging Station Controller and Electric Vehicle Communication Controller by using Power Line Communication (PLC) Module - paramayuda, ronanda; prajogo, tutuko; sinaga, maralo; priandana, eka rakhman; riza (Liaison Journal of Engineering, 2022)
The purpose of this thesis is to design integration, development and functional verification of communication system between DC charging station controller and electric vehicle communication controller by using Power line Communication (PLC) module, Raspberry Pi 4, Pulse Width Modulation (PWM) converter circuit, and CAN Bus communication protocol. The problems that this thesis attempts to solve are transmitting High-Level Communication digital signal data passed through a Low-Level Communication conductor without interfering with one another. Low-Level Communication is in the form of an analog control pilot Pulse Width Modulation (PWM) signal, the signal with a frequency of 1 kHz is used in AC Charging Station. In certain cases, AC Fast Charging and DC Fast Charging require High-Level Communication in the form of digital signal data, this digital signal data is sent using the CAN Bus Protocol with a baud rate of 500 kbps. The communication system between the DC charging station and electric vehicle setup is developed by integrating Raspberry Pi 4 with 2-CH CAN HAT Module as the DC Charging Station Controller and Electric Vehicle Communication Controller, SICON EMI EVPLC Module as Power Line Communication (PLC) Module, and PWM converter circuit as PWM signal converter. According to IEC 61851-1:2017, this setup will carry out the communication system between a DC charging station and an electric vehicle. The setup of communication between the DC charging station and the electric vehicle has been successfully developed, and the Power Line Communication module used in this thesis is successful in transmitting High-Level Communication through a Low-Level communication conductor. The CAN data that has been sent and received by controllers shows the components used in this communication system are successful. Keywords: Electric Vehicle, Charging Station, Power Line Communication, High-Level Communication, CAN Bus Protocol, Pulse Width Modulation, Raspberry Pi 4.